(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
COVID-19 is the biggest challenge facing medicine and scientists in the world in modern times. The highly contagious and severe course of the disease has become a serious test for the global health system.